Social, Sains and Environment Learning Before Covid-19 and The Learning Amid Covid-19 in Nursery Student - Bahagia Bahagia; Rimun wibowo; Fachruddin Majeri Mangunjaya; Budi Susetyo (Universitas Pahlawan Tuanku Tambusai, 2021)
This study aims to find scientific, social and environmental learning before the covid outbreak. Another goal is to find learning strategies during the Covid-19 period and learning priorities and challenges faced by teachers and parents during online learning. The research method approach uses a descriptive qualitative approach. Data were collected by in-depth interviews with Dahlia's early childhood education school teacher. The sample was selected through a purposive technique. The results were carefully examined through triangulation and source triangulation techniques. The results showed that environmental learning was carried out to children through miniatures or animal sculptures in the classroom, then taking school children to the zoo to get to know the animals. When the teacher was in class, he asked again what he had seen in nature. The teacher also takes school children to nature to see the plants and animals in the surrounding environment. Meanwhile, to hone the social session, the teacher makes various games such as role-playing games to become a police officer so that there is a cooperation between students. Then, the teacher also uses outdoor games such as swings where there is social learning because they have to be done together. Another way is to play the role of a policeman and some other students play the role of criminals.